2015
DOI: 10.1310/sci2103-233
|View full text |Cite
|
Sign up to set email alerts
|

Participation and Life Satisfaction in Aged People with Spinal Cord Injury: Does Age at Onset Make a Difference?

Abstract: Background: Few studies have reported on outcomes in samples of elderly people with SCI and the impact of the age at onset of SCI is unclear. Objective: To study levels of participation and life satisfaction in individuals with SCI aged 65 years or older and to analyze differences in participation and life satisfaction scores between individuals injured before or after 50 years of age. Methods: This cross-sectional survey included 128 individuals with SCI who were at least 65 years old. Age at onset was dichot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
9
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 28 publications
6
9
2
Order By: Relevance
“…Our findings are similar to those published by Krause and colleagues reporting lower subjective well-being (as a measure of SWL) in persons with SCI who were non-white 4 and Post et al who found that less education was associated with lower SWL. 5 Our finding that individuals who are not-married report lower SWL is consistent with literature describing this finding in the general population. 24 In addition, in individuals with a traumatically acquired disability, being married predicted greater SWL 27 and overall SWL has been found to be higher for individuals with SCI who are married.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our findings are similar to those published by Krause and colleagues reporting lower subjective well-being (as a measure of SWL) in persons with SCI who were non-white 4 and Post et al who found that less education was associated with lower SWL. 5 Our finding that individuals who are not-married report lower SWL is consistent with literature describing this finding in the general population. 24 In addition, in individuals with a traumatically acquired disability, being married predicted greater SWL 27 and overall SWL has been found to be higher for individuals with SCI who are married.…”
Section: Discussionsupporting
confidence: 92%
“…1 Compared with the general population, individuals with SCI report lower SWL. 2 In general, sustaining a more recent injury, of non-traumatic etiology, older age at injury onset, older chronological age, and having more psychological service needs are associated with lower SWL in the SCI population, 3,4 whereas lower age at injury onset, 5 lower levels of pain 6 and pain interference, 7 active lifestyle, 8 and white race 3 are associated with higher SWL. Furthermore, more active participation in self-care practices and better access to care and care coordination with health care providers are associated with higher SWL in individuals with SCI.…”
Section: Introductionmentioning
confidence: 99%
“…This finding indicates that other factors may also be associated with life satisfaction among older adults who have lived with a SCI for many years. Previous research has suggested significant associations with psychological distress and depression [52], sense of coherence [17], perceived health status [52], and community participation [52,54] in individuals with SCI. Furthermore, engagement in physical activity has demonstrated positive effects on life satisfaction [55].…”
Section: Discussionmentioning
confidence: 99%
“…Post and Reinhart 13 studied life satisfaction and participation in 128 persons with SCI who were all at least 65 years old and investigated differences in relation to age at injury (above or below 50 years of age). This study 13 included older adults with both long-term and short-term injury and showed that longer time since injury was associated with greater life satisfaction. In addition, Krause et al 14 studied changes in life satisfaction among 49 individuals at least 40 years after SCI and mean age of 65 years.…”
Section: Introductionmentioning
confidence: 99%